Pergeseran Paradigma Pesantren dan Tantangan Pengembangan Kultur Pesantren di Era Globalisasi - Agung Ramadhan, Agung Ramadhan; Husni Mubarak, Husni Mubarak; Muhammad Iqna Syam, Muhammad Iqna Syam; Hanafiah, Hanafiah; Muchtarom, Muchtarom (PT. Solusi Komunikasi Terapan, 2024)
As an educational institution, Islamic boarding schools (pesantren) are required to carry out significant acceleration and transformation. If in the past the scope of output was limited to the religious dimension only, now Islamic boarding school graduates are expected to be able to contribute a lot to various aspects of community life. The development of applications in the field of information technology has had a major impact on various areas of life, including creative industries such as printing, digital image processing and graphic design. This requires us to provide training to students so that they can follow developments and be able to use them as provisions after they graduate. Training in using these applications is important to equip students’ creativity so that later when they leave the boarding school they can develop these skills to be more independent. In fact, these skills can also equip students to become entrepreneurs, so they can support the economy. Based on this reality, the author took the initiative to help Islamic boarding schools develop students’ creativity through graphic design training. This is because the human resources that Islamic boarding schools have in the field of graphic design are very minimal or even non-existent. With this graphic design training, it is hoped that it can help Islamic boarding schools in equipping students with skills so that their creativity is formed.